Bothrops erythromelas (Amaral, 1923) venom induces apoptosis on renal tubular epithelial cells. (August 2016) - de Sousa, Fabíola Carine Monteiro; Jorge, Antônio Rafael Coelho; de Menezes, Ramon Róseo Paula Pessoa Bezerra; Torres, Alba Fabíola Costa; Mello, Clarissa Perdigão; Lima, Danya Bandeira; Borges Nojosa, Diva Maria; Havt, Alexandre; Alves, Renata Sousa; Martins, Alice Maria Costa; Monteiro, Helena Serra Azul
Abstract: Bothrops erythromelas is responsible for a large number of snakebite incidents in Northeastern Brazil. Previously, we showed the effects of whole B. erythromelas venom in an isolated kidney model. To continue the study with B. erythromelas venom, the present work aims to study the effects of this venom on MDCK tubular epithelial cells and assess gene expression involved in kidney injury, aiming at elucidating the mechanisms responsible for renal toxicity. Cytotoxicity in MDCK cells showed an IC50 of 93 μg/mL and predominant apoptotic involvement demonstrated by flow cytometry assays and expression of caspase-3 and caspase-8. In conclusion, we suggest that Bothropoides erythromelas venom causes apoptosis with involvement of the caspases, probably through the extrinsic pathway. Highlights: Bothrops erythromelas venom (BeV) is cytotoxicity on epithelial tubular renal cells. BeV stimulated the expression of caspases. BeV induces apoptosis.